Georgia Farmers' Listening Habits - Tom Hallman (Journal of Applied Communications, 1983)
I know you don't like long, tedious narratives. Neither do I. So, very Simply, here's what this report is about: Roland Brooks. Joe Courson and Bob Malleur, Georgia extension's broadcast news specialists, need to know more about their farm audience. When do Georgia farmers listen to the radio? Do they watch their local television news? What kind of agricultural information do they want from the broadcast media?